2018
DOI: 10.11606/issn.1678-4456.bjvras.2018.133413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of somatic cell count on composition and hygiene indicators of bulk tank milk

Abstract: This study evaluated the effect of somatic cell count (SCC) on composition and hygienic quality of dairy herd bulk tank milk -specifically, the effect of SCC of bulk tank of dairy herds on composition (fat, protein, total solids, nonfat dry solids) and on total bacterial count (TBC), psychrotrophic count (PC) and coliform count (CC) were evaluated. A total of 230 dairy herds located south of Minas Gerais and west of São Paulo were selected based on SCC geometric mean obtained from five monthly analyses precedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…A bulk tank SCC greater than a target level (e.g. 250 000 cells/ml) often indicates underlying subclinical mastitis (Lievaart et al ., 2007; Macedo et al ., 2018). Regrettably, and as we have already said, numerous studies have recorded higher levels than this.…”
Section: Heat Stress and Somatic Cell Count (Scc)mentioning
confidence: 99%
See 2 more Smart Citations
“…A bulk tank SCC greater than a target level (e.g. 250 000 cells/ml) often indicates underlying subclinical mastitis (Lievaart et al ., 2007; Macedo et al ., 2018). Regrettably, and as we have already said, numerous studies have recorded higher levels than this.…”
Section: Heat Stress and Somatic Cell Count (Scc)mentioning
confidence: 99%
“…Various time series studies have reported bulk tank SCC above the locally accepted level, e.g. 250 000 cells/ml, in different regions and countries in the world (Lievaart et al ., 2007; Kelly et al ., 2009; Suriyasathaporn et al ., 2012; Hashemzadeh and Khalajzadeh, 2014; DeLong et al ., 2017; Aghamohammadi et al ., 2018; Macedo et al ., 2018). SCC also increases with environmental THI (Nasr and El-Tarabany, 2017), reducing milk value (St-Pierre et al ., 2003; Rhoads et al ., 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different result was reported by Ribas et al (2014), as they observed SNF with increasing SCC increased. Macedo et al (2018) also found that SNF were higher in herds with SCC threshold higher than 250x10 3 cells/ml. Variation in the diffrent results may be due to differences in diet, parity and season of the experiment, management, etc.…”
Section: Resultsmentioning
confidence: 72%
“…High SCC was affected by age of the cow, age of lactation, stress, season, nutrition, observance of hygiene rules and mastitis. The levels of SCC and TVC provide valuable information on the hygienic conditions during various steps of milk production on the farm (Cedden et al 2002;Eyduran et al 2005;Macedo et al 2018;Ginestreti et al 2020). Consumers need to be able to source raw milk from farmers that have adopted a high level of good animal husbandry practices and manufacturing practices that can reduce potential food safety hazards to very low levels (Berge and Baars 2020;Singhal et al 2020).…”
Section: Introductionmentioning
confidence: 99%